Strategi Personal Branding dan Pengaruhnya terhadap Preferensi Elektoral Pemilih pada Pilkada Kota Jambi 2024 - Shela Octarina Putri; Dimasrizal; Muliono; Dimas Subekti (PT. Hasba Edukasi Mandiri, 2026)
This study aims to analyze the personal branding strategy of the Maulana–Diza pair and examine its influence on voters’ electoral preferences in the 2024 Jambi City mayoral election. The research employed a quantitative approach using a survey method with an associative research design. Data were collected through questionnaires distributed to 400 respondents registered as permanent voters (DPT) in Jambi City, selected using probability sampling with a simple random sampling technique. The independent variable in this study was political image, measured through indicators of political identity, authenticity, and emotional closeness, while the dependent variable was voting decision. The findings indicate that political image plays a significant role in shaping voters’ electoral preferences. A clear political identity, consistency between attitudes and actions, and emotional closeness to the community contribute to the formation of voter trust. These results demonstrate that personal branding strategy is a crucial factor influencing voting behavior at the local political level.